(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
This article explores the possibilities of applying linguistic models in the grammatical analysis of pronouns in the process of POS-tagging (Part-of-Speech tagging). The study highlights the significance of pronouns as a part of speech for linguistics and computational linguistics. Methods for determining pronouns using rules, statistical models, and machine learning were examined. The results of the study suggest new methodological approaches for working with pronouns and provide a foundation for further scientific research